Pengenalan Sosio Scientific Issue secara Daring terhadap Kemampuan Penalaran Siswa - Rivanna Citraning Rachmawati; Erma Diningsih (Universitas PGRI Semarang, 2021)
SSI is a strategy that aims to stimulate intellectual, moral and ethical development, as well as awareness of the relationship between science and social life. The use of SSI will improve students' reasoning skills to face the challenges of the 21st century. This SSI application uses questions on social issues. This research was conducted in December 2020. This research used a descriptive survey method. The research stage was carried out with a survey related to students 'reasoning abilities in the city of Semarang, then students were given questions about SSI as a form of treatment and observed how the patterns of students' reasoning abilities were related to SSI. The results showed an increase in students' reasoning abilities due to the introduction of SSI questions.